(untitled) (Politeja, 2025)
Research on microstates in political and administrative sciences and international relations is certainly not popular. Nonetheless, it is worth undertaking such research by focusing on the challenges of their participation in integration processes (especially in economic terms) or issues related to migration (including climate issues). When studying this group of states, appropriate research methods should be used, not always the same as for larger states. Undoubtedly, they are specific actors in international relations, characterised by a small territory, a small population, specific relations with their neighbours, and late participation in international organisations. At present, there are also no grounds to question their sovereignty. Taking into account two factors (size of territory and population), there are twelve microstates in the world.